2020
DOI: 10.1038/s41598-020-74948-3
|View full text |Cite
|
Sign up to set email alerts
|

Increasing temperatures accentuate negative fitness consequences of a marine parasite

Abstract: Infectious diseases are key drivers of wildlife populations and agriculture production, but whether and how climate change will influence disease impacts remains controversial. One of the critical knowledge gaps that prevents resolution of this controversy is a lack of high-quality experimental data, especially in marine systems of significant ecological and economic consequence. Here, we performed a manipulative experiment in which we tested the temperature-dependent effects on Atlantic salmon (Salmo salar) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…Overton et al ( 2018 ) reported that sea lice treatments at cooler temperatures can result in salmon mortalities ranging from 15 to 30%. A recent study showed that “high” levels of lice infestation (6.8 ± 0.4 lice per fish) decreased the survival probability of post-smolt salmon at 19°C by 25% (Godwin et al, 2020 ). In fact, the interpretation that cage-site losses of salmon at high temperatures may result from temperature × pathogen interactions is supported by recent data for other fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Overton et al ( 2018 ) reported that sea lice treatments at cooler temperatures can result in salmon mortalities ranging from 15 to 30%. A recent study showed that “high” levels of lice infestation (6.8 ± 0.4 lice per fish) decreased the survival probability of post-smolt salmon at 19°C by 25% (Godwin et al, 2020 ). In fact, the interpretation that cage-site losses of salmon at high temperatures may result from temperature × pathogen interactions is supported by recent data for other fishes.…”
Section: Discussionmentioning
confidence: 99%
“…The higher treatment years 2017 and 2018 were characterized by warmer fall surface temperatures as noted also by DFO (2018) 47 , a higher freshwater input in spring 47 , 48 , and stronger NE wind conditions. Unlike some salinity thresholds 49 , 50 temperature does not have a limiting effect on louse survival in the ranges observed naturally 16 . Temperature mediated growth of sea lice 51 on the other hand likely affected the severity and recurrence of infestations and consequently the amounts of chemical input.…”
Section: Discussionmentioning
confidence: 82%
“…This highlights the importance of adequate data collection to document treatment approaches including potential link with changing environmental conditions. High sea surface temperature and salinity (> 12 °C and > 12‰) can increase sea lice growth and survival rates 15 with more negative health effects on wild and farmed Atlantic salmon 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Infectious diseases cause significant population declines in wild and captive animals 5 . Small flatworms, such as the Monogenea, are one of the main causes of disease outbreaks and economic losses 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Diseases in highly commercialized species cause significant economic losses every year, especially in the fish farming sector where high densities of stressed animals and poor water quality provides ideal conditions for outbreaks of disease, including those caused by monogeneans 5 , 9 . For this reason, in recent years, the topics of climate change and infectious diseases in aquatic animals have gained special attention, but the evidence regarding the connection is still scarce 10 12 .…”
Section: Introductionmentioning
confidence: 99%